Supplier Audit Information Sharing and Responsible Sourcing - Ha, Albert Y.; Shang, Weixin; Wang, Yunjie (Management Science, 2023)
We develop a game-theoretic model to study the incentive for competing manufacturers to share supplier audit information. Based on the audit information, each manufacturer decides whether to source from a common supplier who has uncertain responsibility violation risk or to switch to a backup supplier who has no responsibility violation risk but charges a higher price. When supplier responsibility violation occurs, some consumers boycott the manufacturers involved. Audit information allows a manufacturer to reduce the uncertainty about the risk of the common supplier. We show that audit information sharing may make the manufacturers’ sourcing strategies more or less differentiated. As a result, the information-sharing decision is not monotone in the model parameters. We fully characterize the manufacturers’ equilibrium audit information-sharing and sourcing decisions and establish conditions under which audit information sharing induces the manufacturers to adopt more or less responsible sourcing strategies. We also show that a manufacturer could be better off when the cost premium of sourcing from the backup supplier or the risk of the common supplier becomes higher or the audit information becomes less accurate. We consider several extensions of the base model and demonstrate that the main insights remain mostly valid. This paper was accepted by Charles Corbett, operations management. Funding: A. Y. Hawas supported by the Wei Lun Foundation. W. Shang was supported by the Research Grants Council of Hong Kong [GRF Project LU 13501415]. Y. Wang was supported by National Natural Science Foundation of China [Grant 71901209]. Supplemental Material: The online appendix is available at https://doi.org/10.1287/mnsc.2022.4358 .